Semiotics of peasants in transition : Slovene villagers and their ethnic relatives in America - Portis-Winner, Irene, 1923- (Sound and meaning., 2002)
Offers a new way of doing ethnography, based on an analysis of interaction between immigrants from a small village in Slovenia to the U.S. and the culture they left.